2018
DOI: 10.1111/jomf.12550
|View full text |Cite
|
Sign up to set email alerts
|

Leaving and Returning Home: A New Approach to Off‐Time Transitions

Abstract: Objective This study offers a new approach to off‐time transitions and applies it to the link between leaving and returning home. Background It is no longer uncommon for young adults to return after having left the parental home. Previous research has mostly examined returning home in isolation from leaving home, although these two transitions are closely intertwined. Method Using longitudinal data from the German Socio‐Economic Panel Study, the authors examine the link between leaving and returning home in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 41 publications
(92 reference statements)
0
10
0
Order By: Relevance
“…Zooming in on separated families, we provided more insight into the role of stepfamily experiences on leaving home. In line with some previous studies, we demonstrated that young adults who grow up with a stepparent are more likely to leave home at a young age compared to young adults from single-parent families (Aquilino, 1991;Blaauboer & Mulder, 2009;Cooney & Mortimer, 1999;Goldscheider & Goldscheider, 1989van den Berg et al, 2018avan den Berg et al, , 2018b. Using recently collected data from the Netherlands that included an oversample of young adults from separated families and stepfamilies, we used detailed measures for both dependent and independent variables.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Zooming in on separated families, we provided more insight into the role of stepfamily experiences on leaving home. In line with some previous studies, we demonstrated that young adults who grow up with a stepparent are more likely to leave home at a young age compared to young adults from single-parent families (Aquilino, 1991;Blaauboer & Mulder, 2009;Cooney & Mortimer, 1999;Goldscheider & Goldscheider, 1989van den Berg et al, 2018avan den Berg et al, , 2018b. Using recently collected data from the Netherlands that included an oversample of young adults from separated families and stepfamilies, we used detailed measures for both dependent and independent variables.…”
Section: Discussionmentioning
confidence: 54%
“…Little is known about explanations for early home-leaving among young adults from stepfamilies. One previous study found that having a partner and residential mobility account for about 20% of the difference in early home-leaving between step-and two-parent families (van den Berg et al, 2018a(van den Berg et al, , 2018b. Two early studies suggest that compared to young adults from single-parent families, young adults from stepfamilies are more likely to leave because of friction than because of a wish to live independently or to live with a partner (Kiernan, 1992;Young, 1987).…”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Both linguistic incorporation and cultural norms vary by immigrant origin (Bean & Stevens, 2003) such that Latin-origin immigrant parents are among the least likely to be English proficient, and therefore may be more likely to rely on their children for linguistic brokering. In the United States, approximately 30% of Spanish-speaking foreign-born are English proficient (speak it "well or very well"), compared with nearly 50% among those who speak a language other than Spanish at home (U.S. Census Bureau, 2017). Furthermore, immigrants originating from Latin American countries are among the most likely to speak a language other than English at home (Portes & Rumbaut, 2006).…”
Section: Prior Research and Theorymentioning
confidence: 99%
“…A large multidisciplinary body of research has extensively detailed the many facets of this transition including its timing and prevalence and changes therein associated with broader social shifts such as women's entry into the labor force (e.g. van den Berg, Kalmijn, and Leopold 2018). These studies have focused nearly exclusively on parental co-residence and family/household formation, with limited engagement of the implications of contact with institutions such as the military, the criminal justice system, and postsecondary education on this milestone.…”
mentioning
confidence: 99%